Perbedaan Pengetahuan, Sikap, dan Keterampilan Kader Lansia dalam Merawat Lansia Hipertensi Sebelum dan Sesudah Pelatihan - Tien Hartini; Eros Siti Suryati; Aan Nurhasanah; Nurdahlia Nurdahlia (Poltekkes Kemenkes Jakarta III, 2021)
The elderly period is a time when the elderlies complain about various kinds of problems that are felt due to their deteriorating body condition. One of the problems experienced by the elderly is hypertension. Apart from being influenced by setbacks, it is also influenced by the lack of knowledge, attitudes, and skills of the family in caring for the elderly, so that it has an impact on the increasing cases of hypertension in the elderly. To control this condition, someone who has the ability and willingness to treat elderly hypertension is needed. This study aims to obtain an overview of the effect of the Parental Assistance Model Training which is: Energetic (Energik), Willing to help (Mau membantu), Active (Aktif), and Patience (Sabar) (POT EMAS) on increasing the ability of elderly cadres in caring for elderly people with hypertension. The research method used is a Quasi experiment without control group design. The sample is elderly cadres, as many as 30 people were determined by purposive sampling technique. Statistical test using dependent t-test. The results showed that the POT EMAS Model training could have a significant effect on increasing knowledge, changing attitudes, and changing the skills of elderly cadres in caring for elderly hypertension. For this reason, the POT EMAS Model can be used as material in carrying out training or refresher for elderly cadres.